La-doped cobalt supported on mesoporous alumina catalysts for improved methane dry reforming and coke mitigation - Tran, Ngoc Thang; Le, Quyet Van; Cuong, Nguyen Van; Nguyen, Trinh Duy; Huy Phuc, Nguyen Huu; Phuong, Pham T.T.; Monir, Minhaj Uddin; Azrina, Abd Aziz; Truong, Quang Duc; Sumaiya, Zainal Abidin; Nanda, Sonil; N. Vo, Dai-Viet
The promotional La2O3 effect on the physicochemical features of mesoporous alumina (MA) supported cobalt catalyst and its catalytic performance for methane dry reforming (MDR) was examined at varied temperature and stoichiometry feedstock. The Co3O4 nanoparticles were evidently scattered on fibrous mesoporous alumina with small crystal size of 8e10 nm. The promotion behavior of La2O3 facilitated H2-reduction by providing higher electron density and enhanced oxygen vacancy in 10%Co/MA. The addition of La2O3 could reduce the apparent activation energy of CH4 consumption; hence, increasing CH4 conversion up to 93.7% at 1073 K. The enhancement of catalytic activity with La2O3 addition was also due to smaller crystallite size, alleviated H2-reduction and the basic character of La2O3. Lanthanum dioxycarbonate transitional phase formed in situ during MDR was accountable for mitigating deposited carbon via redox cycle for 17e30% relying on reaction temperature. Additionally, the oxygen vacancy degree increased to 73.3% with La2O3 promotion. The variation of H2/CO ratios within 0.63e0.99 was preferred for downstream generation of long-chain olefinic hydrocarbons.